Varicella-zoster virus (VZV) open reading frame 10 protein, the homolog of the essential herpes simplex virus protein VP16, is dispensable for VZV replication in vitro. - Cohen, J I (1994)
Varicella-zoster virus (VZV) open reading frame 10 (ORF10) protein in the homolog of the herpes simplex virus type 1 (HSV-1) protein VP16. VZV ORF10 transactivates the VZV IE62 gene and is a tegument protein present in the virion. HSV-1 VP16, a potent transactivator of HSV-1 immediate-early genes and tegument protein, is essential for HSV-1 replication in vitro. To determine whether VZV ORF10 is required for viral replication in vitro, we constructed two VZV mutants which were unable to express ORF10. One mutant had a stop codon after the 61st codon of the ORF10 gene, and the other mutant was deleted for all but the last five codons of the gene. Both VZV mutants grew in cell culture to titers similar to that of the parental virus. To determine whether HSV-1 VP16 alters the growth of VZV, we constructed a VZV mutant in which VP16 was inserted in place of ORF10. Using immune electron microscopy, we found that HSV-1 VP16 was present in the tegument of the recombinant VZV virions. The VZV VP16 substitution mutant produced smaller plaques and grew to a lower titer than parental virus. Thus, VZV ORF10 is not required for growth of the virus in vitro, and substitution of HSV-1 VP16 for VZV ORF10 impairs the growth of VZV.